Analysis of Perceived Ease of Use and Perceived of Usefulness to Enchance Customer Interest in Using BCA Mobile Banking - Diana Sri Putri Anjani; Ida Jalilah Fitria (Journal Of Management Analytical and Solution (JoMAS), 2023)
This study aims to determine the influence of perceived ease of use and perceived usefulness on the intention to use BCA Mobile Banking. The study involved 20 BCA Mobile Banking users as research subjects. The research method used was descriptive-qualitative research. Data collection was conducted through interviews and observations. The results of the study show that perceived ease of use has an influence on the intention to use BCA Mobile Banking. The participants stated that the use of BCA Mobile Banking is easy to understand and does not require significant effort. Perceived usefulness also influences customers' intention to use BCA Mobile Banking. The participants stated that the system and facilities offered provide benefits for them as users. Furthermore, this study found that the more customers believe that Mobile Banking is easy to use, the higher their intention to use it. Similarly, as customers perceive the usefulness and benefits of using Mobile Banking, their intention to use it also increases.